PROTOTIPE E-LEARNING UNTUK PENDALAMAN DAN EVALUASI MATERI PEMBELAJARAN PADA SMPN 1 SAMIGALUH - Ayu Novita; Anik Andriani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
the conventional learning system is face-to-face learning that is still an effective learning method. But there is some weakness in this method, among others limited times for face-to-face, lack of time to evaluation and discussion, because of time lost to the delivery of subject matter. The research purpose is development E-Learning prototype in SMPN1 Samigaluh to complement of conventional learning systems. The stages in building prototype E-Learning apply the stages in prototype models. The stages in building prototype E-Learning apply the stages in prototype models. It’s consisting of three stages, namely, listen to customers, build and repair prototypes, test, and evaluation. In addition, data collection techniques using observation, interview, and literature study are also applied. This is to collect data for making e-learning prototypes. The first stage, listening to customers, and make specification requirements consist of two parts that are functional specification requirements and non-functional specification requirements. The second stage, build and repair system using Entity Relationship Diagrams and Logical Record Structure to design databases. The third stage, testing, and evaluation using customer check to knowing the success of E-Learning prototypes functionality. The result gets E-Learning prototypes to consist of learning material facility, discussion forum, a quiz to evaluation, and evaluation result values.